2007
DOI: 10.1093/jn/137.4.1017
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Flour Fortification Is Unlikely to Benefit the Neediest in Guatemala

Abstract: The potential impact of wheat flour fortification with iron and folic acid was assessed using data about food purchases from the nationally representative 2000 Guatemalan Living Standards Measurement Survey. Of 7265 households, 35% were indigenous and 57% rural; 11% were extremely poor, 35% were poor, and 54% were nonpoor. The percentage of households that purchased wheat flour, sweet bread, French rolls, and sliced bread in the previous 15 d was 10, 88, 59, and 11%, respectively. The median amount of fortifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 29 publications
4
63
0
Order By: Relevance
“…As already noted, the departure point of this study was the 2007 study of Imhoff-Kunsch et al [4]. That study estimated the impact of the Guatemalan wheat flour fortification program using unconditional consumption levels and concluded that the program's impact was minor.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…As already noted, the departure point of this study was the 2007 study of Imhoff-Kunsch et al [4]. That study estimated the impact of the Guatemalan wheat flour fortification program using unconditional consumption levels and concluded that the program's impact was minor.…”
Section: Discussionmentioning
confidence: 87%
“…This is not the first time this type of survey has been used for this purpose in Guatemala. Imhoff-Kunsch et al [4] analyzed the 2000 ENCOVI to assess the potential impact of wheat flour fortification. That study served as a point of departure for the analysis presented here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although evaluations in Guatemala (26) and Sri Lanka (27) showed that flour fortification has little impact on anaemia, in Venezuela compulsory fortification of corn and wheat flours seems to have restored the Fe status of adolescents of low socio-economic status (28) .…”
Section: Discussionmentioning
confidence: 99%
“…In the past, food fortification, diet diversification, and nutrient supplementation have been most frequently used as public health interventions to reduce micronutrient-induced morbidity and mortality worldwide (Suharno et al 1993;Haider et al 2003;Brown et al 2007;Wienecke and Gruenwald 2007;Casey et al 2010;Eneroth et al 2010). However, these approaches have had only limited success and could not by themselves attain sufficiently millennium development goals mainly because such interventions require infrastructure, continuous flow of resources, purchasing power, or access to markets and health care systems to their success, often not available to people living in remote areas (Underwood 1999;Imhoff-Kunsch et al 2007;Ssemakula and Pfeiffer 2011).…”
Section: Introductionmentioning
confidence: 99%